2011
DOI: 10.2119/molmed.2010.00239
|View full text |Cite
|
Sign up to set email alerts
|

Altered Methylation at MicroRNA-Associated CpG Islands in Hereditary and Sporadic Carcinomas: A Methylation-Specific Multiplex Ligation-Dependent Probe Amplification (MS-MLPA)-Based Approach

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that contribute to tumorigenesis by acting as oncogenes or tumor suppressor genes and may be important in the diagnosis, prognosis and treatment of cancer. Many miRNA genes have associated CpG islands, suggesting epigenetic regulation of their expression. Compared with sporadic cancers, the role of miRNAs in hereditary or familial cancer is poorly understood. We investigated 96 colorectal carcinomas, 58 gastric carcinomas and 41 endometrial carcinomas, occurring as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…The tumor-specific promoter methylation of miR-148a, miR-18b and miR-34b/c in cancers other than prostate has already been described. 12,16,17 Recently, miR-542-3p was shown to initiate apoptosis in cancer cells. 18 miR-132's differential expression between normal and tumorous tissues indicates a context-dependent role as either an oncomiR or a tumor suppressor with upregulated expression in lung, 19 breast 20 and tongue carcinomas, 21 and downregulated expression in osteosarcoma 22 and gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor-specific promoter methylation of miR-148a, miR-18b and miR-34b/c in cancers other than prostate has already been described. 12,16,17 Recently, miR-542-3p was shown to initiate apoptosis in cancer cells. 18 miR-132's differential expression between normal and tumorous tissues indicates a context-dependent role as either an oncomiR or a tumor suppressor with upregulated expression in lung, 19 breast 20 and tongue carcinomas, 21 and downregulated expression in osteosarcoma 22 and gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…We opted for a methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA)-based approach, which allows for multiplex, quantitative analysis of methylation in archival formalin-fixed, paraffin-embedded (FFPE) specimens without the need of bisulfite conversion [16]. A representative electropherogram from MS-MLPA analysis is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Saito et al showed that mir-127 was suppressed by promoter hypermethylation and by a decrease in acetyl-H3 and methyl-K4H3 in cancer cells [56]. Genome-wide analysis of different cancer types has shown the influence of DNA methylation and histone modifications on the global regulation of miRNAs [57][58][59].…”
Section: Interplay Between Epigenetic Factorsmentioning
confidence: 99%